Management Incentives under Formula Apportionment - Tax-Induced Distortions of Effort and Compensation in a Principal-Agent Setting - - Jan Thomas Martini; Rainer Niemann; Dirk Simons (Center for Economic Studies and ifo Institute (CESifo), 2014)
The introduction of a common consolidated corporate tax base (CCCTB) and tax allocation via formula apportionment (FA) is hotly debated in the European Union (EU) since more than a decade. While the literature has thoroughly analyzed the economic effects of FA from a macro-level perspective, the firm view has been added only recently. Within this micro-level framework discussing possible tax-induced distortions of multi-jurisdictional entities' (MJE) decisions becomes feasible. Anticipating the reactions of MJEs to the introduction of FA requires considering delegation and incentivisation, because management decisions are influenced by principal agent relationships. How FA affects the demand for managerial effort is a hitherto neglected research question. Accordingly, the objective of this paper is to highlight the tax-induced distortions of managerial incentives caused by FA. For this purpose we set up a LEN-type principal-agent model with agents in two different jurisdictions. Compared to the case with separate taxation (ST) the principal demands increased effort and pays an increased compensation to managers in low-tax jurisdictions, if payroll enters the FA formula. Managers in high-tax jurisdictions face the opposite effect. Further, the composition of the compensation packages changes. Overall, net profit increases, because FA offers potential for profit shifting.
Keywords: H25; M41; 330; common consolidated corporate tax base; formula apportionment; managerial compensation; multi-jurisdictional entities; principal-agent-problem